Klasyfikacja rejonów Poznania ze względu na stopień dotkliwości ubóstwa gospodarstw domowych - Szwarc, Krzysztof (Poznań Regions Classification for the Sake of the Intensity of Poverty in Households, 2009)
The aim of this article is indicating regions in Poznań, which are characterized by the highest intensity of poverty. The main measure of the poverty intensity is a poverty gap indicator. It informs how far (on average) below the poverty line a poor person falls. In percentage it informs what amount of money (in relation to the poverty line) every person should get to leave the poverty zone. In Poznań are 65 socalled auxiliary units. The author calculated the poverty gap indicator for every region. Next, using cluster analysis, the author classified these units according to the similarities in the poverty intensity. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 47, s. 427-433